2023
DOI: 10.21123/bsj.2022.6924
|View full text |Cite
|
Sign up to set email alerts
|

Study the Nuclear Structure of Some Even-Even Ca Isotopes Using the Microscopic Theory

Ban Sabah Hameed,
Tabarak Abdulla Alwan

Abstract: The root-mean square-radius of proton, neutron, matter and charge radii, energy level, inelastic longitudinal form factors, reduced transition probability from the ground state to first-excited 2+ state of even-even isotopes, quadrupole moments, quadrupole deformation parameter, and the occupation numbers for some calcium isotopes for A=42,44,46,48,50 are computed using fp-model space and FPBM interaction. 40Ca nucleus is regarded as the inert core for all isotopes under this model space with valence nucleons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Level density is considered an important parameter in many theoretical studies like astrophysical studies and cross-section calculations reaction rates calculations [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Level density is considered an important parameter in many theoretical studies like astrophysical studies and cross-section calculations reaction rates calculations [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown exotic nuclei to be one of the largest issues in nuclear physics, along with stable nuclei, and has shown a wide variety of novel occurrences. Nuclear physics is developing swiftly as a result of the increased accessibility to uncommon isotopes that differ from stable nuclei in their neutron-proton ratios 3 . Hence, research on mirror nuclei provides a unique viewpoint on how coulomb interaction may affect single-particle wave functions 4 .…”
Section: Introductionmentioning
confidence: 99%